Model Implementasi Inovasi Di Sektor Publik Studi pada Inovasi E-Office Satu Pintu di Puslatbang PKASN LAN - Nugraha, Hari; Nurasa, Heru; Irawati, Ira; Myrna, Rita (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
Innovation is a need for organizations to improve service and performance. Puslatbang PKASN LAN develops the innovation called by one-stop e-office. One-stop e-office are the programs that consist of a website integration program; the official correspondence electronic system; the staffing information system; and the inventory information system. One-stop e-office aims to simplify the office administration to support the implementation of the tasks institution. The programs have developed and maintained to ensure innovation sustainability. One-stop e-office innovation aims to facilitate the implementation of office administration to support the implementation of the tasks and functions of the institution. Therefore, this study aims to analyze how the implementation process of innovation. This study described the implementation model of one-stop e-office innovation in Puslatbang PKASN LAN. The research used a qualitative approach and descriptive method. Data collection techniques used were literature study, in-depth interviews, and observation. The data analysis technique used is descriptive qualitative technique. The innovation is implemented through three stages, namely the generation, acceptance and implementation of ideas. The Factors that drive the innovation implementation are the support from the stakeholders; the availability of competent personnel; the innovation competition climate in LAN; and the technology availability. While the factors that inhibit the innovation are the interest differences between work units; and limited resources for the innovation implementation.